Transient Inactivation of Basolateral Amygdala During Selective Satiation Disrupts Reinforcer Devaluation in Rats. - West, Elizabeth A.; Porcelli, Patrick A.; Mumen, Alice T.; McCue, David L.; Gale, Karen; Malkova, Ludise (Behavioral Neuroscience, 2012)
Basolateral amygdala (BLA) function is critical for flexible, goal-directed behavior, including perfor-mance on reinforcer devaluation tasks. Here we tested, in rats, the hypothesis that BLA is critical for conditioned reinforcer devaluation during the period when the primary reinforcer (food) is being devalued (by feeding it to satiety), but not thereafter for guiding behavioral choices. We used a spatially independent task that used two visual cues, each predicting one of two foods. An instrumental action (lever press) was required for reinforcer delivery. After training, rats received BLA or sham lesions, or cannulae implanted in BLA. Under control conditions (sham lesions, saline infusions), devaluation of one food significanrty decreased responding to the cue associated with that food, when both cues were presented simultaneously during extinction. BLA lesions impaired this devaluation effect. Transient inactivation of BLA by microinfusion of the -γ-aminobutyric acid receptor type A agonist muscimol resulted in an impairment only when BLA was inactivated during satiation. When muscimol was infused after satiation and therefore, BLA was inactivated only during the choice test, rats showed no impairment. Thus, BLA is necessary for registering or updating cues to reflect updated reinforcer values, but not for guiding choices once the value has been updated. Our results are the first to describe the contribution of rat BLA to specific components of reinforcer devaluation and are the first to show impairment in reinforcer devaluation following transient inactivation in the rat.